THE EFFECT OF COOPERATIVE SCRIPT METHOD ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 8 PEKANBARU IN COMPREHENDING RECOUNT TEXTS - Juri Simbolon, Elena Rosinta; Azhar, Fadly; Eliwarti, Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre-experimental study is aimed at finding out if there is a significant effect of Cooperative Script method on the ability of the first year students of SMAN 8 Pekanbaru in comprehending recount texts. The design of the study is one group pre-test-treatment-posttest design. 36 students of class X Math-Science 9 in the second semester of academic year 2017/2018 were chosen as the sample by using cluster random sampling. The instrument of the test was in the form of 40 multiple choice type of questions about recount texts and the treatment was conducted in six times. The students’ scores were analyzed by using SPSS (Statistical Package for the Social Sciences) 23.00 for windows. The results of the data analysis showed that the mean score of pre-test is 70,9028 and the mean score of post-test is 76,2500. The result showed that the value of t-test was higher than t-table (9,619>2,030) at the significance level 5% and at the significance level 2% (9,619>2.438). Therefore, alternative hyphotesis (H1) is accepted and null hyphotesis (Ho) is rejected. It can be concluded that there is a significant effect of Cooperative Script method on the ability of the first year students of SMAN 8 Pekanbaru in comprehending recount texts.Keywords: Effect, Cooperative Script Method, Reading Comprehension